(untitled) - Sorokin, Pitirim Aleksandrovich (New York, 1941)
Contents: Chapter I. The diagnosis of the crisis. II. The crisis of the fine arts; III. The crisis in the system of truth: science, philosophy, and geligion; IV. The crisis in ethics and law...
Keywords: Văn minh,Civilization; Triết học